2018
DOI: 10.1111/joim.12778
|View full text |Cite
|
Sign up to set email alerts
|

Friends and foes of tuberculosis: modulation of protective immunity

Abstract: Protective immunity in tuberculosis (TB) is subject of debate in the TB research community, as this is key to fully understand TB pathogenesis and to develop new promising tools for TB diagnosis and prognosis as well as a more efficient TB vaccine. IFN-γ producing CD4 T cells are key in TB control, but may not be sufficient to provide protection. Additional subsets have been identified that contribute to protection such as multifunctional and cytolytic T-cell subsets, including classical and nonclassical T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 203 publications
0
9
0
Order By: Relevance
“…In TB, defective activation of myeloid cells 8,13 may contribute to impaired TB immunity by suppression of Th1 effector cells and activation of different pathogenic and Treg cell subsets with a large phenotypic and functional heterogeneity, including expression of immune checkpoint molecules, such as IDO, cytotoxic T-lymphocyte-associated protein (CTLA)-4, programmed death ligand 1, and LAG-3. 14 Although excessive inflammation in TB is harmful and an anti-inflammatory response is required to avoid tissue destruction, local polarization of immunosuppressive subsets with poor antibacterial properties may also delay or prevent the clearance of infection, leading to progressive TB disease. We previously found that high iNOS expression in TB granulomas coincides with impaired Th1 and CD8 þ CTL responses but enhance FoxP3 þ Treg cells in patients with active TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In TB, defective activation of myeloid cells 8,13 may contribute to impaired TB immunity by suppression of Th1 effector cells and activation of different pathogenic and Treg cell subsets with a large phenotypic and functional heterogeneity, including expression of immune checkpoint molecules, such as IDO, cytotoxic T-lymphocyte-associated protein (CTLA)-4, programmed death ligand 1, and LAG-3. 14 Although excessive inflammation in TB is harmful and an anti-inflammatory response is required to avoid tissue destruction, local polarization of immunosuppressive subsets with poor antibacterial properties may also delay or prevent the clearance of infection, leading to progressive TB disease. We previously found that high iNOS expression in TB granulomas coincides with impaired Th1 and CD8 þ CTL responses but enhance FoxP3 þ Treg cells in patients with active TB.…”
Section: Discussionmentioning
confidence: 99%
“…12 Mouse data suggest that classically activated proinflammatory macrophages (M1) produce nitric oxide (NO) and engage in bacterial killing as opposed to alternatively activated anti-inflammatory macrophages (M2) that instead use arginase (Arg)-1 to induce fibrosis and prohealing responses. 13,14 The inducible nitric oxide (iNOS) and Arg-1 regulate L-arginine levels in tissue by competing for cellular L-arginine, which is the substrate for both of these enzymes. 15 M1 or M2 polarized macrophages stimulate Th1/cellular or Th2/antibody responses, respectively, which further amplify M1/M2 responses via production of IFN-g or IL-4.…”
mentioning
confidence: 99%
“…As primary reservoirs for intracellular growth and persistence of Mycobacterium tuberculosis (Mtb), macrophages play a critical role in the pathogenesis of tuberculosis (TB) disease. Macrophages comprise a heterogeneous population of cells that are involved in the induction of innate as well as adaptive TB immunity and also contribute to tissue remodeling (1). Polarization of macrophage-like cells from monocytes into phenotypically and functionally different cells occur in response to microenvironmental signals (2,3) that may affect the ability of the cells to control Mtb infection.…”
Section: Introductionmentioning
confidence: 99%
“…There was a failure to use recommended MAP and SBP targets. Seventy‐seven MAP measurements (72.6%) and 50 SBP measurements (47.2%) were lower or higher than international evidence‐based recommendations of 80–90 (NICE, 2014) and 100–140 mmHg (Brighenti & Joosten, 2018; Carney et al, 2016a), respectively. The current practice in trauma ward is to maintain MAP higher than 65 mmHg and SBP higher than 90 mmHg, which is inconsistent with recommendations.…”
Section: Discussionmentioning
confidence: 80%